Reading Newspaper Articles as a Motivation Tool for Students with Nonlinguistic Major - Singatullova, Aliya A.; Sakaeva, Liliya R.; Ismagilova, Guljusa K. (Journal of History Culture and Art Research, 2017)
This article deals with the motives and attitudes of students with nonlinguistic major studying English as a foreign language in a higher educational institution. Nowadays, having a good command of English both oral and written is a prerequisite for a successful promotion in every field, students must learn how to communicate by means of a foreign language on a very high level. The aim of this paper is to show the efficiency of reading activities for motivating students during their studies, as well as to emphasize the relevance of reading authentic newspaper articles. Significance of the work is contained in finding and using new methods and teaching means for improvement of students’ competence in reading in a foreign language. Results of the empirical study conducted by the authors represent evaluation of authentic newspaper articles’ potential for reading comprehension in a classroom and, furthermore, demonstrate effectiveness of this method for EFL and ESL teaching. In other words, the use of authentic text materials from modern Russian and English newspapers with their adaptation and application of various types of communicative tasks before and after the process of reading has been proved to increase the motivation of students to learn English. Reading newspaper articles, therefore, has been also detected to be an effective tool for development of intercultural competences. The experimental part of the investigation was conducted in the Kazan Federal University (Russia), and consisted of a questionnaire that was filled in anonymously by various groups of students, answers to which helped to determine the popularity of reading newspapers among students.